Avoidant personality disorder: Definition, clinical and neurobiological profiles, differential diagnosis and therapeutic framework - Giulio Perrotta (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2021)
This work focuses on the analysis of the general, clinical, neurobiological and therapeutic profiles of the disorder under examination, suggesting a particular attention to the elements that could make a difference in relation to healing or better management of symptoms, often aggravated by frequent comorbidities.